2021
DOI: 10.5465/annals.2019.0031
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Beyond Levels: Advancing Research on Stigmatization

Abstract: Stigma has become an increasingly significant challenge for society. Recognition of this problem is indicated by the growing attention to it within the management literature which has provided illuminating insights. However, stigma has primarily been examined at a single level of analysis: individual, occupational, organizational, or industry. Yet, cultural understandings of what is discreditable or taboo do not come from the individual, occupation, organization, or industry that is stigmatized; on the contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 271 publications
(492 reference statements)
2
131
1
1
Order By: Relevance
“…Involution is not regressive, but creative: "To involve is to form a block that runs its own line 'between' the term in play and beneath assignable relations" (p. 239). Although we lack the space to fully explore these observations, an assemblage ontology has much to contribute to academic conversations in areas such as criminal organizations (Cederström & Fleming, 2016;Vaccaro & Palazzo, 2015), stigmatization (Lashley & Pollock, 2019;Zhang, Wang, Toubiana, & Greenwood, 2020), and categories (Bowker & Star, 1999;Garud, Gehman, & Karnøe, 2010).…”
Section: Assemblage Theory In Organization Studiesmentioning
confidence: 99%
“…Involution is not regressive, but creative: "To involve is to form a block that runs its own line 'between' the term in play and beneath assignable relations" (p. 239). Although we lack the space to fully explore these observations, an assemblage ontology has much to contribute to academic conversations in areas such as criminal organizations (Cederström & Fleming, 2016;Vaccaro & Palazzo, 2015), stigmatization (Lashley & Pollock, 2019;Zhang, Wang, Toubiana, & Greenwood, 2020), and categories (Bowker & Star, 1999;Garud, Gehman, & Karnøe, 2010).…”
Section: Assemblage Theory In Organization Studiesmentioning
confidence: 99%
“…Stigmatization is a phenomenon that transcends the individual level. Effectively addressing anti-Asian coronavirus stigmatization and its effects on psychological well-being will require strategic multi-level management and multi-sectoral engagement (Zhang et al 2020). First, overt manifestations of ethnoracial coronavirus stigmatization should be prevented.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Studies have found that employees who perceive themselves to face occupational stigma experience several negative outcomes (see Kreiner and Mihelcic, 2020 ; Zhang et al, 2021 ; Kreiner et al, 2022 , for review), such as higher occupational and organizational disidentification ( Lai et al, 2012 ; Schaubroeck et al, 2018 ), lower job satisfaction ( Baran et al, 2012 ), increased organizational production deviance behaviors ( Shantz and Booth, 2014 ), and higher turnover intention ( Pinel and Paulin, 2005 ; Lopina et al, 2012 ; Schaubroeck et al, 2018 ). However, other researchers have suggested that perceiving occupational stigma may facilitate more advantageous judgments of the employees themselves and their work, which will lead to positive outcomes ( Helms and Patterson, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ashforth and Kreiner (1999) highlighted a need to understand occupational stigma with reference to occupational prestige (relatively low vs. relatively high) because occupational prestige represents social perceptions of different kinds of work and likely influences the social construction of occupations. However, existing research has primarily focused on typically low-prestige occupations that are stigmatized by the majority of society ( Ashforth et al, 2017 ; Schaubroeck et al, 2018 ; Zhang et al, 2021 ), such as casino employees ( Lai et al, 2012 ), exotic dancers ( Grandy, 2008 ), animal shelter workers ( Baran et al, 2012 ), and garbage collectors ( Peter et al, 2019 ). Occupational stigma may also be directed at high-prestige occupations, such as physicians or teachers.…”
Section: Introductionmentioning
confidence: 99%